Child restraint system use and its associated factors in Shenzhen. (September 2021) - Cai, Weicong; Lei, Lin; Zhou, Haibin; Wang, Yirong; Peng, Ji; Jin, Ye; Deng, Xiao
Highlights: Road traffic crashes are the top cause of injuries and deaths for children in China. Child restraint system (CRS) is effective to protect child passenger safety. There is no national mandatory legislation requiring CRS use in China. Factors affecting the use of CRS were investigated. Mandatory CRS legislation is urgently needed to ensure child passenger safety. Abstract: Child restraint system (CRS) is effective to protect child passenger safety in a motor vehicle crash. However, research on CRS is limited and the use rate of CRS is not high in China. We carried out a cross-sectional study to examine the use of CRS and its associated factors in Shenzhen. Via the method of cluster random sampling, parents who had at least one child aged 0 to 6 and owned a car from nine community health service centers and eight kindergartens were invited to complete the self-administered questionnaire during April and May 2014, including their knowledge of, attitude toward, and use behavior of CRS and socio-demographics. Multivariable logistic regression was used to explore the factors associated with CRS use. A total of 3768 parents participated in the survey, with a mean age of 33.94. Parents' knowledge and attitude regarding CRS were fair, with the mean score of 3.07 and 3.33 out of 6, respectively, and only 22.8% of them used CRS for their child passengers. Children aged below 3 years, drivers owing expensive cars and wearing seatbelts, and parents with higher knowledge and attitude scores had greater likelihoods to use CRS. Moreover, trip frequency and distance were also significantly associated with CRS use. The findings indicate that the use rate of CRS is low in Shenzhen and parents have fair levels of knowledge and attitude regarding CRS use. Comprehensive public education programs and legislative interventions are urgently required to increase the use of CRS and ensure child passenger safety in Shenzhen